Effect of Inflammation on the Process of Stroke Rehabilitation and Poststroke Depression - Fang, Meidan; Zhong, Lili; Jin, Xin; Cui, Ranji; Yang, Wei; Gao, Shuohui; Lv, Jing; Li, Bingjin; Liu, Tongjun (Frontiers in Psychiatry, 2019)
A considerable body of evidence has shown that inflammation plays an important role in the process of stroke rehabilitation and development of poststroke depression (PSD). However, the specific molecular and cellular mechanisms involved remain unclear. In this review, we summarize how neuroinflammation affects stroke rehabilitation and PSD. We mainly focus on the immune/inflammatory response, involving astrocytes, microglia, monocyte-derived macrophages, cytokines (tumor necrosis factor alpha, interleukin 1), and microRNAs (microRNA-124, microRNA 133b). This review provides new insights into the effect of inflammation on the process of stroke rehabilitation and PSD and potentially offer new therapeutic targets of stroke and PSD.